Modeling of Column Apparatus Processes - Boyadjiev, Christo; Doichinova, Maria; Boyadjiev, Boyan; Popova-Krumova, Petya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a new approach for the modeling of chemical and interphase mass transfer processes in industrial column apparatuses, using convection-diffusion and average-concentration models. The convection-diffusion type models are used for a qualitative analysis of the processes and to assess the main, small and slight physical effects, and then reject the slight effects. As a result, the process mechanism can be identified. It also introduces average concentration models for quantitative analysis, which use the average values of the velocity and concentration over the cross-sectional area of the column. The new models are used to analyze different processes (simple and complex chemical reactions, absorption, adsorption and catalytic reactions), and make it possible to model the processes of gas purification with sulfur dioxide, which form the basis of several patents.
Introduction -- Part I: Qualitative Analysis of Column Apparatuses Processes -- One-Phase Processes -- Two-Phase Processes -- Three-Phase Processes -- Part II: Quantitative Analysis of Column Apparatuses Processes -- Column Reactors Modeling -- Interphase Mass Transfer Processes Modeling -- Part III: Computer Calculation Problems -- Perturbation Method Approach -- Two-Coordinate Systems Problem -- Multi-Step Modeling Algorithms -- Part IV: Waste Gases Purification in Column Apparatuses -- Bi-Zonal Absorption Apparatus -- Absorption-Adsorption Method -- Co-Current Apparatus -- Conclusion.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemistry, Technical; Continuum mechanics; Fluid mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Industrial Chemistry; Continuum Mechanics; Engineering Fluid Dynamics